Computer modeling of the basic mechanisms of bridge cranes - N. S. Galdin; O. V. Kurbatskaya; S. V. Eremina (Вестник СибАДИ)
The authors have proved that computer modeling of mechanisms, components and parts of bridge cranes is an important element in forming optimal design decisions of structures in systems of computer-aided engineering. There is presented an algorithm for designing bridge crane, there are identified functional dependences of energy characteristics of the mechanisms of load lifting and movement.